Information timeliness metrics and research progress for 6G network - Jingzhou SUN; Lehan WANG; Yuxuan SUN; Sheng ZHOU; Zhisheng NIU (Dianxin kexue)
In the future 6G network, machine-type communication will dominate the network traffic.Many vertical applications, such as networked autonomous driving and industrial internet of things, will become new growth points.Such applications usually consist of the collection of status information and distribution of control signals, requiring ultra-low latency.However, this requirement is hard to meet with a large number of end nodes and limited communication resources.In view of this confliction, it was pointed out that the freshness of information should be considered in the status update system instead of just latency.Furthermore, according to the degree of utilization of status information, various measures of information freshness were introduced, and related representative work was summarized.Finally, the future research directions of information freshness and key questions that need to be answered were discussed.